Sensing Absence: Everyday Experiences of Ecological Love and Loss - Maryse A.J. Carbo; Anke A.C. Tonnaer; Riyan J.G. van den Born (Conservation & Society)
People all over the world are increasingly confronted with ecological loss and rapidly changing landscapes caused by anthropogenic processes. In this paper, we examine how nature volunteers experience and deal with ecological loss in everyday life in the Netherlands. We do this by focusing on intimate human experiences with nature and more-than-human communities. Our ethnographic methods include sensory ethnography and photo-elicitation techniques. We argue that owing to attentiveness to more-than-human worlds, people’s experiences with nature are increasingly characterised by ambiguity: experiences of love go hand in hand with experiences of loss and absence. Our study shows that there is little space to mourn this sense of loss, which leaves people feeling alienated, both from their social and natural environments. We illuminate the elusiveness of the ghosts of ecological loss, the absences that are sensed in embodied memories but hardly shared. We conclude by arguing that acknowledging the inclusion of humans in a multispecies community is an important step in the act of mourning beyond the human and towards practices and actions of multispecies care.